Volume 9: Oil and Gas Applications; Supercritical CO2 Power Cycles; Wind Energy 2015
DOI: 10.1115/gt2015-43077
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Bottoming Cycle for High Efficiency Combined Cycle Gas Turbine System With Supercritical Carbon Dioxide Power Cycle

Abstract: The supercritical CO2 (S-CO2) power cycle has been receiving attention as one of the future power cycle technology because of its compact configuration and high thermal efficiency at relatively low turbine inlet temperature ranges (450∼750°C). Thus, this low turbine inlet temperature can be suitable for the bottoming cycle of a combined cycle gas turbine because its exhaust temperature range is approximately 500∼600°C. The natural gas combined cycle power plant utilizes mainly steam Rankine cycle as a bottomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 0 publications
2
15
0
Order By: Relevance
“…They found that the partial heating cycle improves by 23.3% to 26.2% the power output generated by the traditional layouts and even marginally improves by 2.6% the power generated by the single flow split with a dual expansion cycle. The power output of the latter was found to be equal to 83% to 86% of that achievable by the dual flow split with a dual expansion cycle, which is consistent with Cho et al [23]. On the other hand, the new concepts devised by the authors could not exceed the power output achieved by the partial heating cycle, which was finally considered the most promising option for a megawatt scale due to the simpler layout, smaller number of components, and simpler operational scheme.…”
Section: Novel S-co 2 Power Cycles For Whrsupporting
confidence: 89%
See 1 more Smart Citation
“…They found that the partial heating cycle improves by 23.3% to 26.2% the power output generated by the traditional layouts and even marginally improves by 2.6% the power generated by the single flow split with a dual expansion cycle. The power output of the latter was found to be equal to 83% to 86% of that achievable by the dual flow split with a dual expansion cycle, which is consistent with Cho et al [23]. On the other hand, the new concepts devised by the authors could not exceed the power output achieved by the partial heating cycle, which was finally considered the most promising option for a megawatt scale due to the simpler layout, smaller number of components, and simpler operational scheme.…”
Section: Novel S-co 2 Power Cycles For Whrsupporting
confidence: 89%
“…These first promising results paved the way for further studies aimed at comparing the performance of the novel s-CO 2 power cycles against that attainable by single or cascaded layouts of traditional s-CO 2 cycles or multi-pressure steam cycles. In this context, one of the earliest and most comprehensive Energies 2020, 13, 370 5 of 31 study is by Cho et al [23], who compared the performance of the novel s-CO 2 power cycles proposed by Kimzey [18] against that attainable by cascaded systems composed of the sequence of recompression or pre-compression and partial heating cycles. In the WHR from a gas turbine having an exhaust temperature of 580 • C, the authors found that the dual flow split with a dual expansion cycle improves by 6.6% to 8.5% the power generated by the cascaded s-CO 2 systems, and even improves by 3.6% the power output of a triple pressure with a reheat steam cycle.…”
Section: Novel S-co 2 Power Cycles For Whrmentioning
confidence: 99%
“…Thereafter, performances of these three cycles were compared with those of combined systems and a partial heating cycle. 29 The results showed that the cycle with dual splitting is the best in terms of the exhaust heat utilization and cycle efficiency. With the purpose to compare different S-CO 2 cycles comprehensively, Kim et al 30 analyzed performances of these cycles in recovering the waste heat.…”
Section: Compact S-co 2 Cyclesmentioning
confidence: 97%
“…To reduce the compressor work of original cycle, the intercooling technology is employed, thus developing a dual heated cascade S-CO 2 cycle with an intercooler, 29,30 as presented in Figures 3 and 4. For simplicity, this configuration is shortly called "intercooling cycle".…”
Section: Cycle Layoutsmentioning
confidence: 99%
“…The CO2 cooler does not operate in the two phase region as in a steam condenser, resulting in a wider temperature gap in this the heat rejection unit and consequently a higher exergy destruction in this section. An outline of the s-CO2 cycle evaluated is provided in Figure 82, with modelling assumptions taken from [110].…”
Section: Supercritical Co2 Cyclementioning
confidence: 99%